PENGARUH STRUKTUR AKTIVA DAN PROFITABILITAS TERHADAP STRUKTUR MODAL PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Tijow, Anggelita Prichilia; Sabijono, Harijanto; Tirayoh, Victorina Z. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Capital structure discusses the allocation in terms of funding, by looking at the amount of capital from loans with capital derived from the owner of the company. Asset structure may affect the capital structure because firms that have large fixed assets, will tend to get a loan because the asset can be used as collateral. With high profits then the company has adequate internal funds as a source of corporate funding. This study aims to determine the effect of asset structure and profitability on capital structure either partially or simultaneously. The object of this research are 22 companies of consumer goods industry sector listed in Indonesia Stock Exchange. Methods of data analysis using multiple linear regression analysis. The results showed that the asset structure has a positive effect on the capital structure, profitability has a negative effect on capital structure, asset structure and profitability simultaneously affect the capital structure.Keywords: asset structure, profitability, capital structure